Johann J. Winckelmann and Aby Warburg: distinct gazeson the ancient and its temp - Pugliese, Vera (Revista Archai, 2025)
The article comes from different receptions of the sculpture group Laocoontesince Antiquity and their reper-cussions in the artistic and theoretical productions about art. This discussion exploits the understanding of the Art History by georges Didi -Huberman, that according to the dialectics in which Johann J. Winckelmann, in the eighteenth century, would go to represent an antithesis to the artistic -historiographical model of giorgio Vasari at the fifteenth century. Winckelmann inaugurated a model that intended to be objective and which theoretical and methodological premises allowed for an out-look to classical antiquity, favouring greek art over Roman art. However, Aby Warburg escapes from the big picture of Art History’s mainstream, proposing a different outlook on the an-cient, under a methodological and theoretical proposal of dif-ferent natures. Thus, the article proposes to stablish a ligne de partage between both art historians about the reception of the ancient by contemporary Art Historiography.“return” to and from the ancient, the classic and the pathos,and the time model in the Art History, which have resulted in such divergent perceptions of Laocoonte. Therefore, the article suggests outlining the question of the repercussion of the differentiation of these three conceptual axis of both art historians about the reception of the ancient by contemporary Art Historiography